A short note on cue validity - Piet van Tuijl; Peter Verboon; Jacques van Lankveld (Methods in Psychology)
In questionnaire development, content validity is usually operationalized by using items that comprehensively express all aspects of the object of measurement. We argue that this often leads to content coverage that is too broad, and that content validity needs pruning down when the intention is to measure conditions or constructs that should be discerned from other conditions or constructs – which is almost always the case. This pruned-down version of content validity we name “cue validity”, signifying the uniqueness of indicators for a construct. We show what negative consequences have been of ignoring cue validity in previously developed questionnaires and illustrate how taking cue validity into account can guide the validation of new questionnaires.